Fin de siècle : Belgische tekeningen, pastels en prenten van 1885 tot 1905. - Lambrechts, Marc; Adriaens-Pannier, Anne; Baudson, Pierre; ASLK-Galerij, Brussel (Brussel : Etienne Van Driessche, 1991)
Vaes, Walter ; Wolles, Lucien ; Pion, Louis ; Lynen, Amédée ; De Witte, Adrien ; Mertens, Charles ; Marechal, François ; Frederic, Léon ; Vloors, Emile ; Marneff, Ernest ; Mellery, Xavier ; Spilliaert, Léon ; Le Brun, Georges ; Claus, Emile ; Ensor, James ; Van Rysselberghe, Theo ; van de Velde, Henry ; et al.
ASLK Galerij, Brussel, 15 maart - 2 juni 1991
kunstcatalogus
Keywords: België